(untitled) - Helle, Laura; Tynjälä, Päivi; Olkinuora, Erkki; Lonka, Kirsti (British Journal of Educational Psychology, 2007)
Background: Advocates of the project method claim that project-based learning inspires student learning. However, it has been claimed that project-based learning environments demand quite a bit of self-regulation on the part of the learner.Aims: Consequently, it was tested whether students scoring low in self-regulation of learning experienced 'friction', an incompatibility between student self-regulation and the demands posed by the learning environment. This would be manifest in cognitive processing and motivation.Samples: The target group consisted of 58 mainly third-year Finnish university students taking a mandatory project course in information systems design. During the project course, student teams completed a commissioned assignment. The study also included a matched nonequivalent comparison group composed of computer science students attending study programmes without a project-based component. Methods: Data were gathered by means of a questionnaire administered at the beginning and end of the project course and it was analysed by between-groups repeated measures ANOVA. In addition, the students on the course were interviewed. Results: Results suggest that the work-based project model in question may indeed have a substantial motivational impact, interestingly benefiting especially those students who scored low in self-regulation.Conclusions: It is argued that we tend to view learning environments too simplistically. In particular, a basic distinction should be made between individual and collaborative learning contexts, since peer scaffolding, group grading and choice of group roles may explain why students scoring low in self-regulation of learning did not encounter friction as expected.
Keywords: apprentissage en groupe; apprentissage par projet; enseignement supérieur; motivation